KUALITAS PELAYANAN PUBLIK PENGURUSAN PASPOR PADA KANTOR IMIGRASI KELAS 1 DI KOTA PEKANBARU - Adni, Dita Fisdian (UIR PRESS, 2018)
Research study describing quality service of passport arrangement that can be seen from activity that had been done in passport arrangement by Imigration Office Class 1 of Pekanbaru. Study problems is how quality services of passport arrangement that had done by Imigration office Class 1 of Pekanbaru. The method used in this research is quantitative descriptive that is using analysis in-depth interviews with several informants that is citizen who already get the service from Immigration Office Class 1 of Pekanbaru for the last 3 (three) years and officers from Immigration Office Class 1 of Pekanbaru about the services of passport arrangement and also using a questionnaire too as a technique of data collection. Result from this research showing that quality services in Imigration office Class 1 of Pekanbaru in passport arrangement is quite good such as technology used in supporting services increasingly sophisticated and servicing of passport arrangement that provided in accordance with the SOP (operational service standards). However, there are some inadequacy. It showed by complaint about a narrow parking lot, the information about passport arrangement for example about time that not clearly.